Characterization and selection of 'Tierra de Campos' lucerne ecotype using a method of identification of new varieties - Morales M.R.; Álvarez S.; Crespo M.C. (Quality in lucerne and medics for animal production, 2001)
For three years a process of characterization and selection of 97 'Tierra de Campos' samples was carried out. Six samples were selected as the most productive and homogeneous regrowth and high leaf/stem ratio. Three of them were suitable for harvesting and the other three were suitable for grazing. A new selection was then made on the six selected lines, seeking the homozygotic ones for different alleles of the locus Pgi-2. These homozygotic groups can be used as mother plants for future synthetic varieties and would incorporate a kind of identification that would differentiate them from other commercial varieties, which would be polymorphic for this isozyme.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)